2012
DOI: 10.1089/thy.2011.0464
|View full text |Cite
|
Sign up to set email alerts
|

Differentiated Thyroid Carcinoma After 131I-MIBG Treatment for Neuroblastoma During Childhood: Description of the First Two Cases

Abstract: Both these cases of DTC after (131)I-MIBG for childhood NBL underline the importance of adequate thyroid protection against radiation exposure during treatment for NBL. Children who have been treated with (131)I-MIBG should be given life-long follow-up, not only with regard to thyroid function, but also with surveillance for the development of thyroid nodules and thyroid cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…Van Santen et al[97] reported 2 cases of subclinical PTC in neuroblastoma survivors treated with 131 I-MIBG 5 and 12 years earlier. In a follow-up study by the same group of investigators, non-palpable thyroid nodules (most being benign nodules <1 cm in size) were found in 9/16 (56%) survivors, including 2 cases of PTC [54].…”
Section: Radiation-induced Thyroid Diseasementioning
confidence: 99%
“…Van Santen et al[97] reported 2 cases of subclinical PTC in neuroblastoma survivors treated with 131 I-MIBG 5 and 12 years earlier. In a follow-up study by the same group of investigators, non-palpable thyroid nodules (most being benign nodules <1 cm in size) were found in 9/16 (56%) survivors, including 2 cases of PTC [54].…”
Section: Radiation-induced Thyroid Diseasementioning
confidence: 99%
“…Cases of exposure in the prenatal period and the resultant development of congenital hypothyroidism and thyroid nodules have been widely reported in the literature [2,3]. Thyroid cancer has been reported in two adolescents receiving radioactive MIBG therapy, and there has been only one publication reporting papillary thyroid carcinoma developing as a result of 131I therapy administered to the mother [4,5]. Here we report a case of hypothyroidism in the 11-year-old child of a mother receiving 131I therapy due to thyroid cancer.…”
Section: Introductionmentioning
confidence: 82%
“…However, data from nuclear accidents have shown an increase in cases of non-immune hypothyroidism and thyroid cancers among exposed individuals [1,6,7]. Thyroid cancer was reported to develop in two adolescents receiving 131I MIBG therapy for neuroblastoma [4]. Cases of congenital hypothyroidism and thyroid cancer have been reported to develop following intrauterine exposure [2,3].…”
Section: Discussionmentioning
confidence: 99%
“…Thyroid cancer has also been reported after treatment with 131 -I-MIBG for neuroblastoma without neck irradiation and despite prophylaxis with potassium iodide [47]. Treatment with 131 -I-MIBG for neuroblastoma has more recently been shown to possibly be associated with POI [48].…”
Section: The Effect Of Radiotherapymentioning
confidence: 99%